Development and psychometric properties of the Stressors in Breast Cancer Scale - Cerezo, M. Victoria; Soria-Reyes, Lorena M.; Pajares, Bella; Gómez-Millán, Jaime; Blanca, María J. (Frontiers in Psychology, 2023)
Background. A diagnosis of breast cancer generates psychological stress, due not only to treatment and its side effects but also to the impact on different areas of the patient's daily life. Although there are instruments for measuring psychological stress in the cancer context, there is currently no tool for assessing stressors specific to breast cancer. Aims. The aim of this study was to develop the Stressors in Breast Cancer Scale (SBCS). Method. A panel of experts evaluated the clarity and relevance of scale items, providing validity evidence based on test content. Psychometric properties of the scale were then analyzed. Results. Validity evidence based on the internal structure of the SBCS was obtained through exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), following a cross-validation strategy. The CFA supported a second-order factor model with five dimensions: physical appearance and sex strains, health and daily difficulties, interpersonal relationship strains, healthcare strains, and worries and concerns about the future. This structure was invariant across two groups distinguished by time from cancer diagnosis (less than 3 years and 3 years or more from diagnosis). Reliability, based on McDonald’s omega and Cronbach’s alpha coefficients, ranged from .83 to .89 for factor scores, and reached .95 for total scores. Validity evidence was also provided by correlations with depression, anxiety, perceived stress, and perceived health and quality of life. Discussion. The results support the use of the SBCS for measuring stress as a stimulus in the breast cancer context. Implications for clinical practice and research are discussed.